Imaging Appearance of SMARCB1 (INI1)-Deficient Sinonasal Carcinoma: A Newly Described Sinonasal Malignancy - Shatzkes, D.R.; Ginsberg, L.E.; Wong, M.; Aiken, A.H.; Branstetter, B.F.; Michel, M.A.; Aygun, N. (American Journal of Neuroradiology, 2016)
SUMMARY: SMARCB1 (INI1)-deficient sinonasal carcinomas were first described in 2014, and this series of 17 cases represents the first imaging description. This tumor is part of a larger group of SMARCB1-deficient neoplasms, characterized by aggressive behavior and a rhabdoid cytopathologic appearance, that affect multiple anatomic sites. Clinical and imaging features overlap considerably with other aggressive sinonasal malignancies such as sinonasal undifferentiated carcinoma, which represents a common initial pathologic diagnosis in this entity. SMARCB1 (INI1)-deficient sinonasal tumors occurred most frequently in the nasoethmoidal region with invasion of the adjacent orbit and anterior cranial fossa. Avid contrast enhancement, intermediate to low T2 signal, and FDG avidity were frequent imaging features. Approximately half of the lesions demonstrated calcification, some with an unusual “hair on end” appearance, suggesting aggressive periosteal reaction.